Application of piercing the corporate veil in investment law - Santoso, Aditya Warman; Ananti, Diva; P. Sianturi, Master Amos (Trigin Publisher, 2024)
In terms of addressing Piercing the Corporate Veil, it’s a law principle that relates to Limited Liability Companies. One of Limited Liability Companies characteristics is a capability to disregard limited liability for the company’s organs, allowing the organs to be personally liable for wrongful acts that harm the company and other. Knowing this concept is important due to the dynamism of business law and investment law, where the company’s organs often engage in actions solely for personal benefit. This is intriguing due to company’s organs cannot be held personally accountable for corporate actions since the company and it’s organs are separate legal entities. Through normative legal research and a legal and conceptual approach, namely the doctrine of Piercing the Corporate Veil, it’s application to the company’s in investment law will be discussed